A two-grid finite element method for nonlinear parabolic integro-differential equations - Chen, Chuanjun; Zhang, Xiaoyan; Zhang, Guodong; Zhang, Yuanyuan (International journal of computer mathematics, 2019)
In this paper, we present a two-grid finite element method (FEM) for a two-dimensional nonlinear parabolic integro-differential equation. We solve a fully nonlinear system on a coarse grid space with a grid size H and derive a rough approximation of the exact solution, and then solve the corresponding linearized problem on a fine grid space with a grid size h. The optimal error estimates in -norm are obtained for spatially the semidiscrete two-grid FEM. Finally, numerical examples are given to testify the efficiency of the method.